RELATIONSHIP OF FOREIGN INSTITUTIONAL OWNERSHIP AND MANAGEMENT INCENTIVES TO TAX AVOIDANCE - Pujiningsih, Sri; Salsabyla, Nisa Aurelya (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine whether foreign institutional ownership and management incentives can prevent tax avoidance practices in companies. The study was carried out on the manufacturing companies registered on IDX in the 2018-2020 period with 150 observations taken from 50 samples of companies. The sample selection used was purposive sampling. The data were analyzed using multiple regression. The results show that ownership of foreign institutions and management incentives negatively affect tax avoidance, which means that both factors can reduce tax avoidance. This result confirms the perspective of the agency theory used. Likewise, this study helps to enrich agency theory through the role of foreign institutional ownership and management incentives in tax avoidance, and it also helps to assist companies in considering these two factors to minimize tax avoidance practices.